Performance improvements in swimming: a multi-disciplinary approach - Wagner, M. C.; Roper, E. A.; Langelier, A. (Journal of Swimming Research, 2014)
There are several facets of the training process that have the potential to influence a swimmer's performance. The purpose of this review is to introduce a holistic model of performance improvement for swimmers which includes the following four components: training, adequate rest and recovery, proper nutritional habits, and positive psychological mechanisms. At the core of the model is discipline which connects each of the four aforementioned components. Within this review we will present an overview of each element and the methods in which each can be applied and emphasized within the coaching setting.